EVALUASI BUTIR SOAL ULANGAN AKHIR SEMESTER GASAL MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN PADA KELAS KHUSUS BAKAT ISTIMEWA OLAHRAGA (BIO) DI SMA NEGERI 4 YOGYAKARTA - Pasca Tri Kaloka dan Sridadi (Jurnal Pendidikan Jasmani Indonesia, 2015)
AbstractEducational success could be seen from the achievement of learning achieved by the learners that was obtainedthrough evaluation. The research aimed to determine: (1) the level of difficulty, (2) different power, (3) and determinethe effectiveness of the distractors or spread of answer pattern of final test of Odd Semester academic year 2013/ 2014 in SMA N 4 Yogyakarta in the Sport Talented Special Class (Bakat Istimewa Olahraga). This research wasdescriptive with ex post facto approach. The population was the students of class XI IPS 3 Sport Talented SpecialClass of 30 students and 2 teachers. The class sample was determined by documentation technique. It coveredquestions A and B with the answer key. The data were collected by the analysis of question point. Data analysis usedITEMAN. The research result showed that: (1) the level of difficulty of question package A and package B was in thedifficult category. Package A difficulty level of the index was (P 0.30) as many as 35 points (72%), while packageB was (P 0.3) of 41 points (82%) categorized as difficult. (2) Power difference of Package A and package B pointswas in the poor category. Different power index of Package A was (D 0) as many as 36 items (42%), while packageB was (D 0) as many as 34 items (68%) in the poor category. (3) Effectiveness of distractor or answer patternspread of Package A of 11 question items was good and 39 question items were not good, while on the package Bfor 6 question items were good and 44 question items were not good.Keywords: question point evaluation, lesson of physical education, sports, and healthAbstrakKeberhasilan pendidikan dapat dilihat dari prestasi belajar yang dicapai peserta didik yang diperoleh melalui kegiatanevaluasiPenelitian ini untuk mengetahui: (1) tingkat kesukaran, (2) daya beda, (3) serta mengetahui efektifitasdistraktor atau penyebaran pola jawaban ulangan akhir semester gasal tahun 2013/2014 di SMA N 4 Yogyakarta diKelas Khusus Bakat Istimewa Olahraga (BIO).Penelitian ini merupakan penelitian diskriptif dengan pendekatan expost facto. Populasinya peserta didik kelas XI IPS 3 Bakat Khusus Bakat Istimewa Olahraga sebanyak 30 orangdan2 guru. Sampel kelas di tentukan dengan teknik dokumentasi.Meliputi paket soalA dan B serta kunci jawaban. Datadikumpulkan dengan analisis butir soal.Analisis data digunakan analisis ITEMAN.Hasil penelitian menunjukkanbahwa: (1) Taraf kesukaran butir soalpaket A dan paket B masuk dalam kategori sukar. Indeks taraf kesukaran PaketA(P0,30) sebanyak 35 butir (72%), sedangkan paket B (P0,3) sebanyak 41 Butir (82%)masukkategori sukar. (2)Daya bedabutir soal Paket A dan paket B masuk dalam kategori jelek. Indeks daya beda Paket A (D0)sebanyak36 butir(42 %), sedangkan paket B(D0) sebanyak 34 butir (68%) masuk kategori jelek. (3) Efektifitas distraktoratau penyebaran pola jawaban padapaket A sebanyak 11 butir soal yang baik dan 39 butir soal yang tidak baik,sedangkan pada paket B sebanyak 6 butir soal yang baik dan 44 butir soal yang tidak baik.Kata kunci :evaluasi butir soal, pelajaran pendidikan jasmani olahraga dan kesehatan